Exploring Islamic Values in Midwifery Care: Exploring the Integration of Islamic Values in Midwifery care - Suryaningsih, Endang Koni; Lesdianti, Kiki; Marlinton, Septi; Nurhidayati, Siti (Universitas Airlangga, 2026)
Background: Pregnant women who maintain psychological resilience during pregnancy and childbirth are less likely to undergo Cesarean sections due to anxiety. Incorporating Islamic principles—such as offering greetings and reciting